Strategies for sustainable agricultural development in the East African highlands - Pender, John L.; Place, Frank; Ehui, Simeon (International Food Policy Research Institute, 1999)
Low agricultural productivity, land degradation and poverty are severe interrelated problems in the East African highlands. While the proximate causes of such problems are relatively well known, the underlying causes are many and complex, and depend upon many site-specific factors that vary greatly across the diverse circumstances of the region. In this paper, we argue that the appropriate strategy for sustainable development depends greatly upon the “pathways of development” that are feasible in a given location. We argue that such development pathways will be largely determined by three factors determining comparative advantage: agricultural potential, access to markets, and population density. We conclude the paper with hypotheses about the priorities for policy intervention to achieve sustainable development in the East African highlands. Among these, we suggest that the highest priority for road and irrigation development should be areas close to urban markets with high agricultural potential; that development of input and output markets and credit systems will be most critical in such areas; that increasing food security through increased food crop production or other means is likely to be a key to realizing the potential for more commercial production; that subsidies on the costs of transporting fertilizer to remote, high-potential, food deficit areas should be considered as a lower cost alternative to food aid; and that intensified and more private use of hillsides and grazing areas for sustainable uses such as tree planting may have potential to achieve more rapid and sustainable development of lower potential areas.